Plant Ecology - Schulze, Ernst-Detlef; Beck, Erwin; Buchmann, Nina; Clemens, Stephan; Müller-Hohenstein, Klaus; Scherer-Lorenzen, Michael (Springer, 2019)
The puzzle illustrates the characteristics of modern Plant Ecology which aims to relate genetic information and molecular physiology with the biological and environmental constraints of plant life across the globe. Many parts of this puzzle are still not well known nor understood. This new edition of “Plant Ecology” aims to bridge these gaps, linking molecular stress physiology with plant performance, identifying processes which drive plant coexistence in plant communities, and assessing interactions of terrestrial ecosystems with their environment under past, current and future conditions.